PENGARUH JUMLAH PENDUDUK, PANJANG JALAN DAN VOLUME KENDARAAN TERHADAP PERTUMBUHAN EKONOMIDI PROVINSI ACEH (STUDI KASUS 5 KOTA) - Muhammad Zuhdi Arifin; T. Zulham (Fakultas Ekonomi dan Bisnis UNSYIAH, 2019)
Abstract This study aims to determine the effect of population, road length and vehicle volume on economic growth in Aceh Province, especially in urban areas where there are five cities in Aceh Province, namely Banda Aceh, Langsa, Lhokseumawe, Sabang and Subulussalam. In this study, the variables used are the variable number of working age population, road length, vehicle volume and economic growth. Data for this study uses panel data from five cities in Aceh Province in the period 2013-2017. The analysis model used is a multiple linear regression model with a testing model of Fixed Effect Model. The results of the fixed model approach indicate that vehicle volume variables and road length have a positive and significant effect on economic growth, while the variable number of working-age population is positively related but not significant to the economic growth of five cities in Aceh province. The results of this study are expected to be an input for the government in increasing infrastructure growth, especially roads, so as to facilitate the mobility of people and goods with increasing volumes of vehicles.Keywords: Population Number, Road Length, Vehicle Volume, Economic Growth.